1974
DOI: 10.1002/bjs.1800610806
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of bile salt reflux and acid secretion in sliding hiatal hernia

Abstract: The role played by gastric fluid refluxed from the stomach into the oesophagus of patients with symutomatic sliding hiatal hernia has been evaluated in terms of gastric bile salt concentration and acid secretion rates. Patients with a peptic stricture had a higher basal acid output than control subjects. Approximately half of both hiatal hernia groups studied had periods of increased total bile salt concentrations either while fasting or following a test meal, This would indicate abnormal pyloric function in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These observations are in agreement with previous workers (15,25). The fact that taurine conjugates are better bound may well have practical relevance since it is these which have been shown to predominate in the gastric contents of patients with gastro-oesophageal reflux (26).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…These observations are in agreement with previous workers (15,25). The fact that taurine conjugates are better bound may well have practical relevance since it is these which have been shown to predominate in the gastric contents of patients with gastro-oesophageal reflux (26).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Studies in man by Gillison et al (1969) have shown that the symptom of heartburn is associated with reflux of duodenal contents into the stomach and oesophagus. Crumplin et al (1974) investigated bile salts in the stomach of patients with symptomatic hiatus hernia and of control subjects. They found an increased incidence of bile salts in the stomach following a meal in patients with hiatus hernia, but there was no single constituent of the bile that was more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Other therapeutic facilities, such as mucosal protecting drugs [26], prokinetic drugs [27,28] or combination therapy of prokinetic drugs and histamine ^-re cep tor antagonists [29], have been demon strated to be less effective than omeprazole in the treatment of these patients. Thus, studies with omeprazole have provided fur ther evidence that acid is the major factor responsible for mucosal damage to the oe sophagus, rejecting the possible contribution of other factors like bile acids [42] or pan creatic juice [43]. At present, sufficient inhi bition of gastric acidity to induce satisfac tory healing rates in patients with reflux oe sophagitis has only been achieved by treat ment with omeprazole.…”
Section: Discussionmentioning
confidence: 99%